Церковна топографія та некрополі Чернігова у ХVІІ–ХVІІІ ст. - Бондар, О.М. (Праці Центру пам’яткознавства, 2014)
Стаття присвячена питанню топографії церков і некрополів Чернігова XVII–XVIII ст. На основі писемних, археологічних і картографічних джерел проаналізовано етапи мурованого й дерев’яного церковного будівництва в міській системі XVII–XVIII ст. Автор робить висновок про те, що за козацьких часів було відновлено частину давньоруських храмів, а поява нових культових комплексів була пов’язана із розвитком міста – відродженням православної віри, зростанням забудованої площі та збільшенням кількості населення. Тому були побудовані церкви на території Форштадту та на Застриженні. В XVII – першій половині XVIII ст. в Чернігові не існувало єдиного міського кладовища, тому небіжчиків ховали біля церков, а центральне кладовище з’явилося лише в другій половині XVIII ст. Статья посвящена вопросу топографии церквей и некрополей Чернигова XVII–XVIII вв. На основе письменных, археологических и картографических источников проанализированы этапы каменного и деревянного церковного строительства в городской системе XVII–XVIII вв. Автор делает вывод о том, что во времена казачества было восстановлено часть древнерусских храмов, а появление новых культовых комплексов было связано с развитием города – возрождением православной веры, ростом застроенной площади и увеличением численности населения. Поэтому были построены церкви на территории Форштадта и Застриженья. В XVII – первой половине XVIII вв. в Чернигове не существовало единого городского кладбища, поэтому покойников хоронили около церквей, а центральное кладбище появилось только во второй половине XVIII в. Article is devoted to the question of the topography of the churches and cemeteries of Chernigov 17th–18th centuries. Basis of the written, archaeological and cartographic sources, the stages of brick and wooden church building in the city system 17th-18th centuries. On the territory of the Fortress were stone church of the Holy Savior, the Saints Boris and Gleb, the All Saints, the Resurrection of the Lord and wood – the Saints Michael and Theodore, the Archangel Michael, the Iona Theologian and the Annunciation. The author concludes that in the time of the Cossacks was restored part of ancient temples, and the emergence of new religious complex was associated with the development of the city It was the revival of the Orthodox faith, the increased of built up area and population increased. Because were built churches in the territory in Forshtadt and in Zastrizhenya. It was a wooden church – St. Nicholas, Holy Cross, Holy Intercession of the Virgin, the Epiphany, the Ascension of Christ, the Candlemas, the St. Barbara. In the suburb were standing stone churches - St. Catherine, St. Paraskeva Patnitsa. They were appearing along the main streets of the city Chernigiv wasn’t single city cemetery in17th – the fi rst half of the 18th century. Because the dead were buried near the church, and the central cemetery appeared only in the second half of the 18th century. This cemetery was located near the cemetery 12th–13th centuries. In some ways, topography churches and cemeteries 17th–18th centuries repeated topography churches period of ancient Russia. This was due to the historical inheritance of this city.